Comparação dos tempos de geração e digitação de laudos radiológicos entre um sistema eletrônico baseado em voz sobre IP(VOIP) e um sistema tradicional baseado em papel - Ferreira, Dácio Miranda [UNIFESP] (2009)
The patient medical record is extremely important in medicine. The radiology report generation process can be improved using electronic models based in communication and information technologies that can improve productivity, reduce time and cost. This research compares generation and transcription times of the radiology report between a radiology information system where the radiologist can record radiology reports by voice in digital format and the traditional system in which the radiologist writes the radiology reoport by hands. To conduct the study was necessary to model and construct the electronic system for comparison with the existing traditional system. Using forms, radiologists and transcriptionists register the generation and transcription times in both systems. Comparign the averages, the electronic system reduced 20% (p=0,0410) the generation average time of radiology report compared with traditional system. Moreover, the traditional system was more efficient in relation to transcription time whereas the average time of eletronic system was three times bigger (p<0,0001).